المقاربة بالكفاءات وتنمية مهارات التواصل الشفوي باللغة العربية لدى متعلمي السنة الخامسة ابتدائي - وشن, دلال; جيلاخ, ياسين; رحومة, كريمة (University of Eloued جامعة الوادي, 2024)
تحظى اللغة العربية بأهمية بالغة في التعليم، لذا قامت المنظومة التربوية في الجزائر بعدة إصلاحات وتغييرات من أجل إصلاح تعليمها وتعلمها ؛ وهذا بغية الرفع من قيمتها وجعلها مواكبة للتطورات التي تحيط بها من كل جانب، وفي خضم هذه التغييرات نجد اعتماد الجزائر منذ استقلالها على عدة مقاربات بيداغوجية، بدأ بالمقاربة بالمحتويات أو المضامين وصولا إلى المقاربة بالأهداف إلا إن التعليم في ضوء هاتين المقاربتين تميز بالقصور الذي ميز العملية التعلمية، فالتدريس بالمحتويات يقوم على أساس التلقين أما المقاربة بالأهداف فتقوم على منطق التعليم أي تحقيق الهدف، ثم جاءت المقاربة بالكفاءات التي تقوم على التكوين وبعث الحيوية في التعليم. ومن المعلوم أن التعبير الشفوي في المرحلة الابتدائية يأخذ أهميته من أهمية اللغة العربية في تلك المرحلة وبعد الهدف الأساسي لها والمهارات اللغوية جميعها في خدمته فهو من أرقى أشكال الاتصال والتواصل؛ فالهدف من التعبير الشفهي هو تمكين المتعلم من اكتساب المهارات الخاصة بالحديث والمناقشة البناءة فهو وسيلة الاكتشاف والتعلم، كما يدخل في كل الأنشطة التعلمية إما خادما لها أو مخدوما منها. وقد جاءت هذه الدراسة المعنونة المقاربة بالكفاءات وتنمية مهارات التواصل الشفوي باللغة العربية لدى متعلمي السنة الخامسة ابتدائي، لتجيب عن تساؤل رئيس وهو : كيف تؤدي المقاربة بالكفاءات إلى تنمية مهارات التواصل الشفوي لدى متعلمي السنة الخامسة ابتدائي؟ وقد حاولنا الإجابة عن هذا الإشكال من خلال بناء استبيان موجه إلى معلمي السنة الخامسة للوقوف على مدى تحقق مهارات التواصل الشفوي عن طريق المقاربة بالكفاءات؟ ومن خلال استقرائنا لنتائج الاستبيان يتبين بوضوح أن القصور لم يكن في اعتماد المقاربة بالكفاءات كبديل عن طرائق أخرى بقدر ما كان في طريقة تطبيقه فقد كان لعدم توفير أسباب نجاحه من كادر بشري مؤهل وأسباب موضوعية تتعلق بتوفير الأسباب المادية لإنجاح مثل هذه المقاربة عموما ونشاط التعبير الشفهي خصوصا مما يحتم إعادة النظر في كيفية تطبيقه وتوفير الشروط اللازمة لذلك حتى يتسنى لنا الحكم الموضوعي عليه بالنجاح أو الفشل. The Arabic language holds significant importance in education. Thus, the educational system in Algeria has implemented several reforms and changes to improve its teaching and learning, aiming to enhance its value and ensure it keeps pace with surrounding developments. Amid these changes, Algeria has relied on various pedagogical approaches since its independence, starting with the content-based approach and objectives-based approach. However, education under these two approaches was marked by shortcomings; the content-based approach relies on rote learning, while the objectives-based approach focuses on achieving specific goals. Subsequently, the competency-based approach emerged, emphasizing formation and revitalization in education. It Is known that oral expression in the primary stage derives its importance from the significance of the Arabic language at that stage and is considered its main goal. All language skills serve oral expression, which is among the highest forms of communication. The goal of oral expression is to enable learners to acquire the skills necessary for constructive conversation and discussion, serving as a means of discovery and learning. It is involved in all learning activities, either serving them or being served by them. This study, titled The Competency-Based Approach and Developing Oral Communication Skills in Arabic among Fifth Grade Primary Students, aims to answer the main question: How does the competency-based approach lead to the development of oral communication skills among fifth-grade primary students? As researchers, we attempted to address this issue by designing a questionnaire directed at fifth-grade teachers to determine whether the competency-based approach has effectively developed oral communication skills. From our analysis of the questionnaire results, it is evident that the shortcomings were not due to the adoption of the competency-based approach as an alternative to other methods but rather in its implementation. The lack of qualified personnel and material resources necessary for the success of such an approach, particularly in oral expression activities, necessitates reconsidering its application and providing the necessary conditions to objectively assess its success or failure.
لسانيات عامة
Keywords: المقاربة بالكفاءات - تنمية - مهارات - التواصل الشفوي - التعليم الابتدائي; Competency-Based Approach. Development; Skills; Oral Communication; Primary Education.